Frequency/Voltage Regulation with STATCOM with Battery in High Voltage Transmission System. Issue 27 (2016) - Park, Jaeyoung; Yu, Jungwook; Kim, Jungsoo; Kim, Minho; Kim, Kwangrae; Han, Soohee
Abstract: This paper proposes a method of regulating frequency and bus voltage simultaneously with STATCOM with battery in an high voltage transmission system. Comparative analysis of stand-alone STATCOM and STATCOM with battery is carried out to compare the steady state characteristics of them. Dynamic model and controller are designed to accomplish the two control objectives, frequency and voltage regulation. The results are verified in MATLAB on an modified IEEE 14 bus test system.